Atomic layer deposition of rhodium and palladium thin film using low-concentration ozone - Zou, Yiming (2022)
Rhodium (Rh) and palladium (Pd) thin films have been fabricated using an atomic layer deposition (ALD) process using Rh(acac)3 and Pd(hfac)2 as the respective precursors and using short-pulse low-concentration ozone as the co-reactant. This method of fabrication does away with the need for combustible reactants such as hydrogen or oxygen, either as a precursor or as an annealing agent. All previous studies using only ozone could not yield metallic films, and required post treatment using hydrogen or oxygen. In this work, it was discovered that the concentration level of ozone used in the ALD process was critical in determining whether the pure metal film was formed, and whether the metal film was oxidized. By controlling the ozone concentration under a critical limit, the fabrication of these noble metal films was successful. Rhodium thin films were deposited between 200 and 220 °C, whereas palladium thin films were deposited between 180 and 220 °C. A precisely controlled low ozone concentration of 1.22 g m-3 was applied to prevent the oxidation of the noble metallic film, and to ensure fast growth rates of 0.42 Å per cycle for Rh, and 0.22 Å per cycle for Pd. When low-concentration ozone was applied to react with ligand, no excess ozone was available to oxidize the metal products. The surfaces of deposited films obtained the RMS roughness values of 0.30 nm for Rh and 0.13 nm for Pd films. The resistivities of 18 nm Rh and 22 nm Pd thin films were 17 μΩ cm and 63 μΩ cm.